Recent advancements toward the understanding and control of turbulent flows (Summary of ICJWSF2013) - Kuniaki TOYODA; Riho HIRAMOTO (Journal of Fluid Science and Technology, 2014)
The 4th International Conference on Jets, Wakes and Separated Flows (ICJWSF2013) was held in Nagoya, Japan, in September 2013. Advanced papers were presented at the conference, contributing to the progress of the research. This report is a summary of the published papers, focusing on turbulent flows. The papers are classified to seven fields: generation of turbulence fields, free shear flows, separated flows, wall shear flows, multi-physics flows, fluid machinery, and numerical methods/bio-fluid mechanics. The research works in each field are reviewed, noting the contribution to the understanding and control of turbulent flows. For generation of turbulent fields, the unique features of fractal-grid turbulence are discussed by the results of DNS and experiments. For free shear flows, the fundamental features are investigated, and various flow-control methods are demonstrated in engineering applications. For separated flows, many studies on separation control are presented, especially demonstrating the effectiveness of plasma actuators. For wall shear flows, the latest works are presented, revisiting the characteristics of statics and turbulent structures by the recent results of DNS and experiments. For multi-physics flows, the studies for engineering applications are presented in the fields of multiphase flows, reacting flows related to combustion, and aeroacoustics. The results suggest useful ideas to develop innovative technologies in each field. For fluid machinery, interesting studies of wind turbines are presented to increase efficiency. In conclusions, the contribution of the conference is summarized and the future issues on the research of turbulent flows are mentioned.